LESÕES CERVICAIS NÃO CARIOSAS- UMA REVISÃO DE LITERATURA - Portela, Ana Luisa Gomes (2024)
Non-carious cervical lesions (NCCLs) are an increasingly common pathological condition in modern dental practice. They result in the loss of dental tissue in the cementoenamel junction region and have multifactorial etiologies, such as abrasion, attrition, abfraction, and biocorrosion. With the increase in population longevity and changes in lifestyle habits, these lesions are observed more frequently. In addition, they can cause dentin hypersensitivity, aesthetic dissatisfaction, and impaired quality of life (Martins et al., 2022). The research used a narrative review of the literature based on articles published between 2018 and 2024, selected from the PUBMED, SCIELO, and BVS databases. The descriptors used included: “non-carious cervical lesion”, “biocorrosion”, “friction”, and “dental attrition”. Inclusion criteria included full and open access articles, and exclusion criteria included theses, dissertations, and monographs (Galvão and Pereira, 2019). The studies analyzed indicated that NCCLs are a multifactorial condition, with abfraction, caused by eccentric occlusal forces, being one of the main etiologies. Abrasion, often associated with inadequate brushing techniques, also plays a relevant role. Attrition and biocorrosion were identified as other important causes. In addition, cervical dentin hypersensitivity was a common symptom in patients, as well as aesthetic dissatisfaction, especially in visible teeth (Silva et al., 2023). It was concluded that NCCLs represent a multifactorial pathology that negatively affects the oral health of patients. Early diagnosis and the adoption of adequate preventive and therapeutic strategies are essential to prevent the worsening of lesions and improve the quality of life of patients. Multidisciplinary approaches that combine innovations in restorative materials with knowledge of etiologies are essential to ensure better results (Lima et al., 2022).   Keywords: Non-carious cervical lesions; Abfraction; Cervical dentin hypersensitivity; Attrition; Biocorrosion.